TEACHING YOUNG LEARNERS FOREIGN LANGUAGES: STRATEGIES AND ACTIVITIES - Raxmonova Gavxar Nuritdinovna; Rasilova Aziza Isroil qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Teaching foreign languages to young learners presents unique challenges and opportunities. This article explores effective strategies and activities that can enhance the language acquisition process in children. By understanding the cognitive, social, and emotional development of young learners, educators can create engaging and effective language learning environments. The article outlines practical activities that cater to different learning styles and emphasizes the importance of a supportive atmosphere in fostering language skills.